Combined diffusion‐relaxometry MRI to identify dysfunction in the human placenta. Issue 1 (18th March 2019) - Slator, Paddy J.; Hutter, Jana; Palombo, Marco; Jackson, Laurence H.; Ho, Alison; Panagiotaki, Eleftheria; Chappell, Lucy C.; Rutherford, Mary A.; Hajnal, Joseph V.; Alexander, Daniel C.
Abstract : Purpose: A combined diffusion‐relaxometry MR acquisition and analysis pipeline for in vivo human placenta, which allows for exploration of coupling between T 2 * and apparent diffusion coefficient (ADC) measurements in a sub 10‐minute scan time. Methods: We present a novel acquisition combining a diffusion prepared spin echo with subsequent gradient echoes. The placentas of 17 pregnant women were scanned in vivo, including both healthy controls and participants with various pregnancy complications. We estimate the joint T 2 * ‐ADC spectra using an inverse Laplace transform. Results: T 2 * ‐ADC spectra demonstrate clear quantitative separation between normal and dysfunctional placentas. Conclusions: Combined T 2 * ‐diffusivity MRI is promising for assessing fetal and maternal health during pregnancy. The T 2 * ‐ADC spectrum potentially provides additional information on tissue microstructure, compared to measuring these two contrasts separately. The presented method is immediately applicable to the study of other organs.